Pelatihan Kemampuan Percakapan Sehari-Hari Menggunakan Simple Tense Pada Siswa Kelas V SD Islam Bandar Kidul - Nurrahma, Avinta Ika; Damayanti, Ervina; Rahma Nabilla Agustin, Rosi (LOSARI DIGITAL, 2024)
The purpose of this project is to assess students' proficiency with the Simple Present Tense in everyday speech. This activity was intended for 35 Bandar Kidul Islamic Elementary School fifth graders. A pre-test, material discussion, games, practice questions, and a post-test are all part of this English language proficiency exercise. This exercise was conducted in accordance with the findings of earlier observations and pre-tests. The exam results indicate that most pupils are still struggling to learn how to use the Simple Present Tense. With a fresh learning environment and enjoyable teaching strategies, students may comprehend Simple Present Tense sentence structures as a consequence of this practice. Additionally, pupils are able to apply